Księga Ruth - w kierunku nowego biblijnego feminizmu - Graczyk, Waldemar (Teologia i Moralność, 2018)
The Book of Ruth is one of the shortest books of the Old Testament, but it gives the believer one of the most important truths of the Christian faith, that is, faith in Divine Providence. Through the history of simple women, Ruth and Naomi, the inspired author shows that God works in the daily routine of man in his intricate fate, which sometimes seems to contradict God’s goodness. The trust of Ruth and Naomi makes their common destiny illuminated by God, who acts not only in great and spectacular salvific events. The Lord reveals His presence in the world by the people who are sent to those who appear to be rejected by him. Women become figures of faith and trust in God. The article, based on the analysis of the Book of Ruth, shows a woman as an example of trust in Divine Providence. Woman’s trust turns out to be the basis of a close relationship with God, which a man can learn from his life partner. This kind of total devotion to God by a woman can also be a sign of God’s fidelity to every human being. So, based on the Book of Ruth, we can create a theory of some kind of biblical feminism that is perfectly morally healthy, because it is based on faith in God, His providence and love, and not on false faith in human capacities and abilities.